Implementasi layanan bimbingan dan konseling dalam mengatasi permasalahan bullying - Nurussakinah Daulay; Mutiara Aulia; Nadila Nadila; Siska Ardilla Anggaraini; Siti Maila Faiza Tanjung; Irma Diani Hashibuan (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
The study aims to see the implementation of guidance and counseling asa problem-solving effort bullying students at the school-nizam medan. Through field research researchers have tried to describe the cases of bullying that occurred in the field by carrying out sociometry support activities to measure relationships between peers and by performing written interviews through the castee given to the student so that researchers have obtained information and information about the school's bullying. Studies show the importance of implementation of guidance and counseling as an effort to correct bullying. In this case, the role of the bk teacher is indispensable in rendering service and support activities to correct the bullying problem. The general purpose of the study is to address the problem of bullying so as to address school guidance and counseling so that the study can run in the lancer with no student and school barriers.